Upaya Menjaga Kestabilan dan Optimalisasi Jalur Distribusi Komoditas Strategis dalam Pengendalian Inflasi di Provinsi Papua Pegunungan - Meri Berliana; Alber Tulak; Inrianti Inrianti (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This research aims to make efforts to maintain stability and optimize distribution channels for strategic commodities in controlling inflation in the Papua Mountain Province. The data used in this research is secondary data sourced from BPS and BRS. Secondary data in this research is data regarding changes in inflation from April to September 2024. The highest inflation occurred in June at 5.65% with a CPI of 111.29%. The method used in this research is qualitative descriptive research which utilizes literature, journals and official BI news from various related sources. The research results show a high level of inflation in the Papua Mountain Province as a newly expanded province. The government and BI must synergize by carrying out cheap market operations, carrying out market and distributor inspections, realizing BLT, strengthening domestic food security through the Food Estate Program, handling the impact of natural disasters and accelerating the development of agricultural infrastructure and expanding cooperation between regions and the center. To control the inflation rate in the Papua Mountain Province.